2010
DOI: 10.1111/j.1365-3083.2010.02410.x
|View full text |Cite
|
Sign up to set email alerts
|

Passive Acquisition of Protective Antibodies Reactive with Bordetella pertussis in Newborns via Placental Transfer and Breast‐feeding

Abstract: Although acquisition of anti‐pertussis antibodies by the newborn via placental transfer has been demonstrated, a subsequent recrudescence of pertussis infection is often observed, particularly in infants. The present study investigated the passive transfer of anti‐pertussis IgG and IgA antibodies to term newborns and their ability to neutralize bacterial pathogenicity in an in vivo experimental model using mice intracerebrally challenged with viable Bordetella pertussis. Forty paired samples of maternal/umbili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 44 publications
2
12
1
3
Order By: Relevance
“…5,6 The prevalence of recent pertussis infections in pregnant women could be compared with the prevalence found in 2003 because of the equivalence between the cut-offs for detecting recent pertussis infections of both tests. 10,11,25,26 Nevertheless, the anti-PT titers found in recently infected women in this study (117−210 IU/mL) were significantly different than those in women who had not been recently infected (2−89 IU/mL). First, the prevalence of recent pertussis infections in pregnant women was determined using IgG-PT >100 IU/mL in cord blood samples.…”
Section: Discussioncontrasting
confidence: 71%
“…5,6 The prevalence of recent pertussis infections in pregnant women could be compared with the prevalence found in 2003 because of the equivalence between the cut-offs for detecting recent pertussis infections of both tests. 10,11,25,26 Nevertheless, the anti-PT titers found in recently infected women in this study (117−210 IU/mL) were significantly different than those in women who had not been recently infected (2−89 IU/mL). First, the prevalence of recent pertussis infections in pregnant women was determined using IgG-PT >100 IU/mL in cord blood samples.…”
Section: Discussioncontrasting
confidence: 71%
“…These studies have demonstrated that human milk has antibodies against Shigella, Salmonella typhimurium, Campylobacter, Vibrio cholerae, Haemophilus influenzae, Streptococcus pneumoniae, Bordetella pertussis, respiratory syncytial virus, HIV, and other pathogens. 7,75 Epidemiological data indicate that exclusively breastfed children are better protected against a variety of infections 76 and apparently also against celiac disease in childhood 77 as well as allergies and asthma, 78 although studies on the latter issue still show discrepant data. 79,80 It is known that the risk of death from diarrhea can be reduced from 14 to 24 times in infants fed human milk, and that the frequency of diarrhea increases as the milk is replaced by other sources, until full weaning.…”
Section: Breast Milk Cellsmentioning
confidence: 95%
“…The results were expressed in mg/dL. The total IgA antibodies present in the maternal colostrum were measured by ELISA as previously described 12, and the results were expressed in g/L.…”
Section: Methodsmentioning
confidence: 99%